2012
DOI: 10.1111/j.1475-4983.2012.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

The fossil record of Glypturus Stimpson, 1866 (Crustacea, Decapoda, Axiidea, Callianassidae) revisited, with notes on palaeoecology and palaeobiogeography

Abstract: The fossil record of the callianassid genus Glypturus (Decapoda, Axiidea) is re-evaluated. Our systematic revision, both of extant and fossil taxa, is based on major cheliped morphology only, thus providing an important impetus for palaeontological studies. Both spination and tuberculation of chelipeds are herein considered of great taxonomic importance. Presence of spines on the upper margins of the merus and propodus and the lower margin of the carpus are significant for generic assignment, whereas the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 64 publications
(117 reference statements)
0
30
0
Order By: Relevance
“…It has been argued that at least for some genera the morphology of the major propodus can be diagnostic on the genus level (Hyžný 2012; Hyžný & Müller 2012). In this respect, the revision of the ghost shrimp fossil record is ongoing (Hyžný & Müller 2010, 2012; Hyžný 2012; Hyžný & Hudáčková 2012; Hyžný & Karasawa 2012; Hyžný et al 2013). This paper is intended to be a part of the revision and its goal is to discuss in detail assignment of fossil taxa to Calliax based on the case study of Callianassa michelottii A.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that at least for some genera the morphology of the major propodus can be diagnostic on the genus level (Hyžný 2012; Hyžný & Müller 2012). In this respect, the revision of the ghost shrimp fossil record is ongoing (Hyžný & Müller 2010, 2012; Hyžný 2012; Hyžný & Hudáčková 2012; Hyžný & Karasawa 2012; Hyžný et al 2013). This paper is intended to be a part of the revision and its goal is to discuss in detail assignment of fossil taxa to Calliax based on the case study of Callianassa michelottii A.…”
Section: Introductionmentioning
confidence: 99%
“…Today, no ghost shrimp are known from long-lived brackish lakes. Nevertheless, the fossil record of the Central Paratethys ghost shrimp is rather robust ( Hyžný and Müller, 2010, 2012; Hyžný, 2011, 2012a,b; Hyžný and Hudáčková, 2012; Hyžný and Dulai, 2014 ); thus, their persistence in Lake Pannon after seaway closure can be expected, although no callianassid body fossils from the Upper Miocene of the study area have been found so far. The adaptations of ghost shrimps as discussed in chapter 4.1.2 demonstrate that this animal group has abilities to utilize new ecological niches.…”
Section: Discussionmentioning
confidence: 98%
“…Glypturus Stimpson, 1866: 46.-Manning, 1987: 390.-Manning and Felder, 1991: 778.-Sakai, 1999a: 72.-Sakai, 2005b: 130-132.-Sakai, 2011. -Hyžný and Müller, 2012: 969-971.-Hyžný et al, 2013: 133.-Klompmaker et al, 2015: 11.-Komai et al, 2015.…”
Section: Glypturus Stimpson 1866mentioning
confidence: 99%